Space-time Gets Reversed Only for Fermions where as Space-time is Identical for Bosons: Scientific Explanation - Debnath, Prasenjit (Current Approaches in Science and Technology Research Vol. 10, 2021)
In particle physics, there are primarily two sorts of particles. These are bosons and fermions, respectively. Particles are divided into subcategories in both of them. A fermion is a particle that has odd half-integer spin, for example, like \(\frac{1}{2}\) , \(\frac{3}{2}\) and so on. Quarks, Leptons, Protons, Neutrons are fermions. Bosons are particles with integer spins such as 0, 1, 2, and so on. For example, Bosons are like Photons, Gluons, W+, W-, Z0 bosons, Higgs bosons, Mesons etc. All matter particles (with mass) are fermions and have a significant amount. All particles that carry force are bosons. In this chapter, I'll illustrate that only fermions interact with space-time and get reversed. In space-time, bosons interact but are not reversed. Anti-particles (fermions) have space-time reversed, but bosons have space-time that is identical. As a result, all matter particles have their anti-particle counterparts, but all force carrying particles do not have their anti-particle counterparts.